SAMARQAND VILOYATI QURILISH SOHASINING AMALDAGI HOLATI VA ISTIQBOLDAGI RIVOJLANISHI (Marketing Journal, 2026)
AbstractThis article presents a comprehensive analysis of the current state of theSamarkand regionʼs construction industry and its development trends. The studyexamined the volume of construction work completed in the region, the constructionof residential and social infrastructure facilities, the level of development of thebuilding materials industry, and investment activity indicators. Urban developmentprojects, the use of innovative and digital technologies, export potential, and futuredevelopment trends were also analyzed. The articleʼs findings allow us to determine the impact of the Samarkand regionʼs construction industry on the regional economyand its role in sustainable development.Keywords: Samarkand region, construction sector, urban development,infrastructure, investment, building materials, housing construction, innovation,economic development, sustainable growth.